15 km staggered-start Nordic ski races in 2001-18 winter Olympics and World Championships: champions` tactics analysis - Shvetsov, A. V.; Nikishin, I. V.; Matveyev, A. E.; Kleshchev, V. V. (Theory and Practice of Physical Culture, 2019)
The key tactical fitness component in cyclic endurance sports is the choice of a rational tactical pattern (option) of covering the distance and the use of this tactical pattern depending on the competitive situation. In this regard, objective of the study was to analyze the dynamics of competitive speed at the distance of 15 km in the world-class racing skiers, which enabled to identify the optimal cross-country skiing tactics able to become an important factor in increasing the effectiveness of competitive activity and athletic training process. For this purpose, we processed the data of the final protocols of the World Championships and Winter Olympic Games from 2001 in 15 km ski races from a staggered start, which made it possible to determine the indicators of competitive speed (average and at distance segments) and its dynamics. The study showed that the world-class racing skiers choose a rational tactical pattern of covering the 15 km distance from a staggered start depending on the level of their athletic fitness as well as a large number of specific aspects of cross-country skiing and competitive activity. Most often, in the 15 km stag-gered start cross-country skiing race, the world-class racing skiers use the tactical pattern of "maximum initial acceleration" followed by a smooth (or pronounced) decrease in the competitive speed up to the finish line. This is logical from the point of view of energy supply, as with an increase in the duration of competitive activity, there is also a gradual transition from energy-intensive substrates of glycogen stored in the liver and muscles to less energy-intensive fatty acids. Therefore, the main tactical actions of racing skiers in the 15 km ski races from a staggered start are: powerful starting acceleration, warming-up time, reaching near-maximum speed (at the level between maximal oxygen consumption and anaerobic thresh-old), and the ability to maintain this speed as long as possible, withstanding fatigue to the maximum degree. It is this model of speed dynamics at the distance that the authors recommend reproducing during trainings and competitions.